Does job-search assistance affect search effort and outcomes? A microeconometric analysis of public versus private search methods - Denis Fougère; Jacqueline Pradel; Muriel Roger (Institute for the Study of Labor (IZA), 2005)
In this paper, we examine the disincentive effects of the public employment service on the search effort of unemployed workers and on their exit rate from unemployment. For that purpose, we specify a structural search model with fixed and variable costs of search in which unemployed workers select their optimal search intensity given the exogenous arrival rate of job offers coming from the public employment agency. Because the theoretical effect of an increase in this exogenous job offer arrival rate on the structural exit rate from unemployment is ambiguous, we estimate this model using individual unemployment duration data. Our results show that the exit rate from unemployment increases with the arrival rate of job contacts obtained by the public employment service, especially for low-educated and low-skilled workers. They also show that the search effort is more costly for low-educated women and low-skilled adult unemployed workers. This last result suggests that a public employment agency that matches searchers and employers is beneficial, in the sense that it saves searchers in terms of search costs they would otherwise bear.
Keywords: C41; J64; 330; job search; search intensity; public employment agency; simulated maximum likelihood